Environmental Risks and Ecological Sustainability to Eco Practicum in Mining and Energy. (2015) - Radosavljević, Slobodan; Radosavljević, Milan; Radosavljević, Jovana
Abstract: Ecological changes in the dynamics of knowledge over time become part of the ever-faster overall changes and development of different concepts of scientific and technological progress. The recent development and application of ecological knowledge in different areas of activity, have led to changes but with the opening questions of qualitative thresholds achieved in the context of continuous compounding increase and ecological risk potential eco destruction and eco damage. The current concept of promoting eco eco knowledge, creativity and eco Eco skills in the forms of implementation options and determination. If eco is not elementary based on the results of science, do not respect the existence and needs of eco application of the results of scientific research into practice, it will more or less stagnant and still be past his waist. There is a need to explicitly promote institutional and valued ecological scientific thought as the most nationally well with eco creative predisposition rational configuration, high quality of funds and other professional scientific basis. Emergency situations that have emerged in recent years have opened up a number of issues related to the problems of environmental safety of people and the efficient functioning of the system of environmental protection, ecological opportunities for preventive action and to prepare the public for a response to any environmental emergency situations. The current environmental events further proof that no country, regardless of the level of economic and social development can not and must not ignore the threat of eco and eco risks to humans, natural and material resources and the environment in general. There are numerous areas in the local and regional level in the world, for which it can be said that the eco-risk and ecological crisis, ecological insecure with severe negative synergy, a number of problems when it comes to the quality of the environment in these areas. In this paper we analyze the real part of the environmental problems in terms of ecological sustainability, quality and potential ecological risks in terms of the overall ecological safety and its practical operation in the mining industry regionally, level.